Effects of organic acids on the preservation and feeding value of dry and high-moisture milo - Cox, O.J.; Bolsen, K.K.; Riley, Jack G.; Sauer, D.B. (Kansas State University. Agricultural Experiment Station, 2011)
The four milo treatments studied were: (1) artificially dried, (2) artificially dried+ organic acids, (3) high-moisture ensiled and (4) high-moisture + organic acids. The dry milo and high-moisture milo contained 14 and 24 percent moisture, respectively. Milo in treatments 1, 2, and 4 was stored in unlined concrete bins; milo in treatment 3 was ensiled in an air-tight silo.
Keywords: Beef; Milo; Steers; Organic acids